Aceh Special Autonomy Funding Sustainability in Supporting National Resilience - Herman Fithra; Riyandhi Praza; Asrul Fahmi; Deassy Siska (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Aceh has been given the eligibility to manage its own territory and government called special autonomy as one of Helsinki MoU compensation. Moreover, special autonomy fund also presents for Aceh in funding infrastructural development and maintenance, people empowerment, poverty eradication, education, social and health that lasts in five years’ time according to existing policy. This research analysed the Aceh special autonomy fund sustainability in supporting national resilience. In analysing the case, descriptive analysis was conducted through identifying existing issues and solution to the issues on both local and national perspective that predominantly on national perspective. The identified issues were less seriousness of Aceh government elite in managing the fund, unclear mechanism in its implementation and less participation of people. The solution offered to the issues were more consistent and appropriate plan for funding implementation, more focus on non-oil and gas allocation, people development concentrated plan.